Behaviour of Cleavage Properties of Small Clear Laminated Acacia Hybrid Species of Sarawak - Davidson Sating, Riang (Universiti Malaysia Sarawak (UNIMAS), 2020)
The aim of this research to determine the behaviour properties of small clear laminated Acacia hybrid species of Sarawak. The realisation has grown that many earth's resources are non-renewable. Hence, it is important to develop a more economical construction that is eco-friendly and long-lasting product. Therefore, timber such as Acacia mangium and Acacia auriculiformis are selected for study purpose as they are fast-growing time, durable and high strength properties. These properties are the main reason Acacia mangium and Acacia auriculiformis are one of the resources suitable used for construction. In this study, the Acacia mangium and Acacia auriculiformis are combined, forming Acacia hybrid. Then, the Acacia hybrid was laminated with different years which are, 7 years with 10 years, 7 years with 13 years, and 10 years with 13 years. Basic information on physical and mechanical properties for introducing good use of Acacia hybrid species of Sarawak was tabulated to determine the best cleavage properties result of the combination. The relationship between density, moisture content and cleavage properties of small clear specimens were investigated for each group of age combination. The relationship of Acacia between physical properties and mechanical are directly proportional. As proved by Dr. Alik Duju, the relationship between moisture content and density are linear regression. The basic density is lower as the moisture content is higher. The cleavage strength properties of timber also affected by the change of density and moisture content. Strength properties of timber is lower as the basic density become lower. The strength of Acacia hybrid can be increased throughout detail study and effective further laboratory works. All data are analysed by using statistical analysis, where the graph and line graph used to compare the value on each combination with significant level of 95%. The average value or mean, standard deviation, and variance also calculated for each group of combination to analyse more detail of the strength of combination.